2011
DOI: 10.1161/circinterventions.110.959791
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Ultrasound Findings of Early Stent Thrombosis After Primary Percutaneous Intervention in Acute Myocardial Infarction

Abstract: Background-Small stent area and residual inflow/outflow disease have been reported as the strongest intravascular ultrasound (IVUS) predictors of early stent thrombosis (ST) in patients with stable angina. IVUS predictors of early ST in patients with acute myocardial infarction have not been studied. Methods and Results-In the Harmonizing Outcomes with Revascularization and Stents in Acute MyocardialInfarction (HORIZONS-AMI) study, a formal substudy included poststent and 13-month follow-up IVUS at 36 centers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(58 citation statements)
references
References 26 publications
(44 reference statements)
2
52
0
Order By: Relevance
“…21 Conversely, deeper dissections may be associated with an increased risk of target lesion revascularization and type 4a MI, as suggested by literature data. 3,5,24,25 Tissue prolapse was also observed at a very high rate in our study. The prognostic impact of changing the procedural strategy in response to prolapse remains unclear, although there is some evidence to suggest that prolapse may have a deleterious impact.…”
Section: Discussionsupporting
confidence: 70%
“…21 Conversely, deeper dissections may be associated with an increased risk of target lesion revascularization and type 4a MI, as suggested by literature data. 3,5,24,25 Tissue prolapse was also observed at a very high rate in our study. The prognostic impact of changing the procedural strategy in response to prolapse remains unclear, although there is some evidence to suggest that prolapse may have a deleterious impact.…”
Section: Discussionsupporting
confidence: 70%
“…Procedural parameters such as total stent length and the degree of stent expansion have been associated with increased risk of restenosis and thrombosis following PCI [7, 8]. A number of studies have proposed different IVUS cutoffs (i.e., minimal stent cross-sectional area or diameter), which in turn have predicted repeat revascularizations after drug-eluting stent DES and bare-metal stent deployment [4, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent dissections and slow flow, thrombus, stent underexpansion, tissue prolapse, and residual stenosis have been suggested as procedure-related contributing factors to stent thrombosis (27-30). Of these factors, we experienced persistent dissection and stent underexpansion.…”
Section: Discussionmentioning
confidence: 99%
“…Although coronary dissection after percutaneous coronary intervention is not a rare complication, its detection and precise evaluation have an impact in a clinical setting, as it has been reported that coronary dissections are associated with adverse cardiovascular events (30,31). A pathological study suggested that exposure of connective tissue to blood speckle in the lumen due to dissection may result in the progression of thrombus formation (32).…”
Section: Discussionmentioning
confidence: 99%